Shear capacity prediction of buckling-restrained SPSWs with beam-connected only using response surface method. (February 2023) - Tan, Ji-Ke; Zhou, Yang; Peng, Tang; Wang, Yu-Hang; Wang, Kang; Duan, Lin-Li; Yu, Jie
Abstract: The cold-formed steel (CFS) buckling-restrained steel plate shear walls (BRSPSW) with beam-connected only have the characteristics of avoiding additional force on the frame column, flexible arrangement and excellent seismic performance, and can also facilitate the realization of the building function of heat preservation and sound insulation. This study aims to investigate the cyclic shear behaviour of CFS BRSPSW with beam-connected only experimentally and numerically. Firstly, two 1:3 scale specimens were designed and tested. The experimental results showed that the CFS BRSPSW with beam-connected only is a good lateral force resistant structural system. Moreover, the yield shear capacity of the specimen was increased by 10.4% after the hat-shaped CFS stiffeners were arranged. Afterwards, a finite element (FE) model was performed and validated against experimental results in terms of failure modes and hysteresis curves. Based on the validated FE model, two specimens were supplementary analysed to obtain a relatively efficient spacing of CFS stiffeners. To effectively improve the accuracy and efficiency in the early design stage, the response surface method (RSM) was introduced to predict the shear capacity of CFS BRSPSWs with beam-connected only in this study. The results show that the RSM prediction model can accurately predict the shear capacity of CFS BRSPSWs with beam-connected only, and can also effectively improve the accuracy and efficiency in the early design stage - the mean value of the FE calculation results to the response surface prediction results is 1.00, and the coefficient of variation (COV) is 0.0003.